Effects of breeder age, broiler strain, and eggshell temperature on development and physiological status of embryos and hatchlings - Nangsuay, A.; Meijerhof, R.; Van Den Anker, I.; Heetkamp, M. J.W.; Morita, V. De Souza [UNESP]; Kemp, B.; Van Den Brand, H. (Elsevier, 2016)
Breeder age and broiler strain can influence the availability of nutrients and oxygen, particularly through differences in yolk size and shell conductance. We hypothesized that these egg characteristics might affect embryonic responses to changes in eggshell temperature (EST). This study aimed to investigate the effect of breeder age, broiler strain, and EST on development and physiological status of embryos. A study was designed as a 2 × 2 × 2 factorial arrangement using 4 batches of 1,116 hatching eggs of 2 flock ages at 29 to 30 wk (young) and 54 to 55 wk (old) of Ross 308 and Cobb 500. EST of 37.8 (normal) or 38.9°C (high) was applied from incubation d 7 (E7) until hatching. The results showed that breeder age rather than broiler strain had an influence on yolk size (P = 0.043). The shell conductance was higher in Ross 308 than in Cobb 500 (P < 0.001). A high EST resulted in a higher yolk free body mass (YFBM) compared to the normal EST at E14 and E16, but at 3 h after hatch YFBM was lower when eggs were incubated at high EST compared to normal EST (all P < 0.001). Cobb 500 eggs yielded embryos with a lower YFBM at E14, E18, and 3 h after hatch (all P < 0.05) than Ross 308 eggs. Breeder age had no effect on YFBM, but the RSY weight was higher in embryos from the old flock compared to the young flock embryos at E14 and E16 (both P < 0.05). A 3-way interaction among breeder age, strain, and EST was found, especially for incubation duration, navel quality, and relative heart and stomach weights at 3 h after hatch (all P < 0.05). Based on the results obtained, we conclude that oxygen availability rather than nutrient availability determines embryonic development, and the egg characteristics affected embryonic responses to changes of EST, especially for variables related to chick quality.
Keywords: Breeder age; Broiler strain; Eggshell temperature; Embryonic development